Individual variability in cardiac biomarker release after high intensity rowing in elite and amateur athletes - Carranza García, Luis Enrique; Legaz Arrese, Alejandro; Ochoa Ahmed, Fernando Alberto; Vinacua Salvo, César; Muñoz Iriarte, Patricia; Ceballos Gurrola, Oswaldo
The release of cardiac biomarkers with exercise has been previously suggested, however the influence of training level in continuous strenuous efforts in rowing is currently unknown.